Assessment of salivary flow rate and antioxidant levels in ectodermal dysplasia patients: An In vivo study - Aravind Mohanan; Balagopal R Varma; Suresh Kumar; Parvathy Kumaran; Arun Mamachan Xavier (Wolters Kluwer Medknow Publications, 2019)
Aims: To assess the salivary flow rate levels and total antioxidant levels in ectodermal dysplasia (ED) patients and to compare with normal individuals. Materials and Methods: Unstimulated saliva sample of control and case were collected from the mouth to a pre-weighed Eppendorf tube using a Pasteur pipette for 4 min. Stimulated saliva of case and control was also collected after chewing paraffin wax for 30 s. Both the Eppendorf tubes were weighed again after collection of both the saliva samples. The flow rate was calculated as difference of weight of the tube divided by time (4 min). Both unstimulated and stimulated saliva was also separately collected for estimation for total antioxidant levels. Statistical analysis: For intergroup comparison, Mann-Whitney test was used, and for intragroup comparison, Wilcoxon signed-rank test was used. Results: In the intergroup comparison of both the salivary flow rate and total antioxidant levels, there was no statistically significant difference; however, there was statistically significant difference in the intragroup comparison of salivary flow rate and total antioxidant levels in case group. Conclusions: There was a diminished unstimulated salivary flow rate in ED group, but stimulated salivary flow rate was significantly high and the total antioxidant levels in unstimulated saliva of the case group were significantly higher than the stimulated antioxidant levels.